Conflict on the Determination and Confirmation of the Boundary of Nagari Sungai Buluh District, Batang Anai District, Padang Pariaman Regency - Rian Ramadhana; Elfitra; Bob Alfiandi (International Journal of Science and Society, 2021)
The purpose of this study is to describe the reasons for refusal to define and confirm the boundaries of the area in Nagari Sungai Buluh. This article is based on a qualitative case study conducted using in-depth interviews and observation data collection methods. The conflict between Nagari Sungai Buluh and Nagari Sungai Buluh Selatan has occurred since the issuance of Minister of Home Affairs Regulation (Permendagri) number 45 of 2016 concerning the establishment and confirmation of village boundaries which mandates each local government to establish and confirm village boundaries. Based on the regulation of the Minister of Home Affairs, Nagari Sungai Buluh Selatan has determined the boundaries of the administrative area with the original village before the expansion, namely Nagari Sungai Buluh (main), this can be seen from the 2012 customary density decision letter of the nagari, but when it will confirm the boundaries These problems arise, one of which is not receiving the results of the initial agreement.